What's New in SCLC? A Review - Oronsky, Bryan; Reid, Tony R.; Oronsky, Arnold; Carter, Corey A. (Neoplasia (New York, N.Y.), 2017)
A few years ago the answer to the question in the title of this review would have been, “unfortunately not much” or even “nothing”, likely eliciting knowing nods of agreement from oncologists. For the last 3 decades, SCLC has been notorious for its lack of progress, as drug after drug, over 60 of them, in fact, including inhibitors of VEGF, IGFR, mTOR, EGFR and HGF has failed and fallen by the wayside due to little or no impact on PFS or OS, while SCLC's cousin, NSCLC, has notched success after success with a spate of targeted treatment and immunotherapy regulatory approvals. However, a paradigm shift or, more appropriately, a ‘paradigm nudge’ is quietly underway in extensive stage SCLC with a series of agents that in early clinical trials have shown the potential to ‘lift the curse’ in SCLC, heretofore referred to as “a graveyard for drug development”. These agents, constituting the “best of what's new” in SCLC, and discussed in this review following a brief overview of the classification, epidemiology, prognosis and current treatment of SCLC, include checkpoint inhibitors, antibody-drug conjugates, PARP inhibitors, epigenetic inhibitor/innate immune activator, and an inhibitor of RNA polymerase II. Compared to NSCLC, the therapeutic options are still limited but with one or more successes to build momentum and drive long-overdue R&D and clinical investment the hope is that the approval floodgates may finally open.